Existence of a periodic solutions for certain system of nonlinear integro-differential equations - R. Butris (College of Education for Pure Sciences, 2008)
In this paper we investigate the existence and approximation of the periodic solutions for certain systems of nonlinear integro-differential equations, by using the method of successive periodic approximation of ordinary differential equations which is given by A. M. Samoilenko. Also these investigation lead us to the improving the extending the above method.